An Analysis of the Effects of Lao Agricultural Products on the Demand for Chinese Market on the Distribution of Income in Rural Areas - Xaiseepheng, Bounmek (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research is attempted to evaluate the impact of Laos-China railway by focusing on household income in the rural areas of Lao PDR, and also it is analyzed the Chinese market’s demand on specified 4 Lao agricultural products especially cassava, banana, rubber and sugarcane. Moreover, this study compares between Lao farmers who are exported and not exported the agricultural products to the Chinese market. Further, the 3 main econometric models which are utilized in this research including firstly: (DiD) difference-in-differences, secondly, (OLS) ordinary least squares and thirdly, Gini Decomposition analysis by using the data of the year 2019 and 2025. The research has found the export trends of rural households’ agricultural products to the Chinese market increased after the railway. However, there are not all households in the rural areas of Laos received the advantage from the railway, before the railway opened there was 40% poorest households experience to measure increase their income. In this important point to find in this research is that not all poor households did not get the benefit from the increasing of agricultural products export to the Chinese market by using the Laos-China railway and also not all the higher-income households did not get the benefit from the agricultural exports. Finally, the result shows that infrastructure improvement is able to increase the agricultural export and increase the income of rural households.